Integrating fundamental and technical analysis with Maqāṣid al-Sharī‘ah in evaluating JII70 Sharia stock investment performance in Indonesia - Jumarni, Jumarni; Ariska, Ayu; Kadir, Syahruddin (Journal of Islamic Economics Lariba, 2026)
IntroductionThe Islamic capital market in Indonesia has grown rapidly, marked by rising market capitalization, expanding investor participation, and increasing interest in sharia-compliant stocks listed in the Jakarta Islamic Index 70. Despite this progress, many investors still face difficulties in evaluating sharia stocks because investment decisions often rely either on financial fundamentals or short-term market sentiment. This condition creates a need for an integrated model that combines fundamental analysis, technical analysis, and maqāṣid al-sharī‘ah values, particularly wealth preservation.ObjectivesThis study aims to evaluate the investment performance of selected Jakarta Islamic Index 70 sharia stocks by integrating fundamental and technical analysis with the maqāṣid al-sharī‘ah principle of ḥifẓ al-māl. It also examines how financial ratios and market trendiness influence sharia stock price formation.MethodThis study used a descriptive mixed-methods approach based on secondary data from five selected sharia-compliant issuers: PT Aneka Tambang Tbk, PT Alamtri Resources Indonesia Tbk, PT Pertamina Geothermal Energy Tbk, PT Bumi Resources Minerals Tbk, and PT Telkom Indonesia (Persero) Tbk. Fundamental analysis was conducted using price earnings ratio, price to book value, return on equity, earnings per share, and debt to equity ratio. Technical analysis employed moving average, relative strength index, moving average convergence divergence, trading volume, and support-resistance indicators. The study also applied the Integrated Islamic Investment Framework and panel data regression using a fixed effects model.ResultsThe findings show that PT Aneka Tambang Tbk achieved the strongest fundamental score, followed by PT Alamtri Resources Indonesia Tbk and PT Telkom Indonesia (Persero) Tbk. In contrast, PT Bumi Resources Minerals Tbk ranked highest technically as a strong momentum stock. Regression results indicate that price to book value, earnings per share, and trading volume positively affect stock prices, while debt to equity ratio has a negative effect.ImplicationsThe study shows that sharia stock investment requires a balance between profitability, market timing, risk control, and ethical wealth preservation.Originality/NoveltyThis study contributes an integrated Islamic stock evaluation model that links fundamental strength, technical momentum, market trendiness, and maqāṣid al-sharī‘ah-based wealth preservation.